2000
DOI: 10.1046/j.1469-8137.2000.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to extreme low light in the fern Trichomanes speciosum

Abstract: Trichomanes speciosum is a threatened species restricted to sheltered, very humid sites. Uniquely amongst European ferns, differing ecological tolerances of the gametophyte and sporophyte generations are manifested as widely differing distributions. The perennial, vegetatively propagating gametophyte persists in drier, colder, darker habitats than the sporophyte. In sites where the gametophyte grows, light availability was found to be 1 µmol m −# s −" for approx. 85% of daylight hours, rarely or (in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 15 publications
1
44
2
5
Order By: Relevance
“…and Trichomanes speciosum Willd., species with habitat requirements that are different from, and much more demanding than, those of P. spinulosa. Trichomanes speciosum was described recently as ''the most shade tolerant of all plant species so far studied'' (Johnson et al 2000) and the sporophyte generation is restricted to sheltered and extremely humid sites (Ratcliffe et al 1993). While it is not the intention to suggest that P. stricta is equally demanding, it was striking that more open positions where there was luxuriant growth of P. punctata (and where P. spinulosa might have been expected based on experience in the British Isles) were not occupied by P. stricta.…”
Section: Resultsmentioning
confidence: 99%
“…and Trichomanes speciosum Willd., species with habitat requirements that are different from, and much more demanding than, those of P. spinulosa. Trichomanes speciosum was described recently as ''the most shade tolerant of all plant species so far studied'' (Johnson et al 2000) and the sporophyte generation is restricted to sheltered and extremely humid sites (Ratcliffe et al 1993). While it is not the intention to suggest that P. stricta is equally demanding, it was striking that more open positions where there was luxuriant growth of P. punctata (and where P. spinulosa might have been expected based on experience in the British Isles) were not occupied by P. stricta.…”
Section: Resultsmentioning
confidence: 99%
“…Johnson et al (2000) reported that Trichomanes speciosum, a European fern species, grew under 0.01% sunlight condition. Actually, at a leaf ornament farm in Kumamoto, Japan, they grow the plants under 85% shading condition.…”
Section: S S N 2349-0837mentioning
confidence: 99%
“…Por tanto, aunque la escala de origen de las variables no coincidiera, se ajustaron todas las capas ráster para que tuvieran una resolución espacial de 5 m. Ciencias Naturales de Sestao, 2001), en zonas cercanas a regatas (Felipe-Díaz et al, 2012). Su fase gametofítica, independiente de la esporofítica, no posee tales requerimientos ecológicos (Johnson et al, 2000;Macgomol & Sheffield, 2001), por lo que se conocen poblaciones gametofíticas de V. speciosa en el centro de Europa (Krippel, 2001;Krukowski & Swierkosz, 2005) en zonas con condiciones en las que el esporofito no puede subsistir. Todas estas características hacen que este helecho se encuentre catalogado como vulnerable en el Catálogo Vasco de especies amenazadas y en la Lista Roja de la Flora Vascular de la Comunidad Autónoma del País Vasco (CAPV) y está incluido en el Anexo II de la Directiva Há-bitat (Aizpuru et al, 2010).…”
Section: Materials Y Métodosunclassified